The Ideological Upheaval of Stakeholders in Online News about AI as CEO - Farady, Rustono Marta; Panggabean, Hana; Sunaringsih, Monica Sri; Qorib, Fathul; Bangun, Nurlina (Nyimak: Journal of Communication, 2025)
In today's digital age, a more critical approach is needed to understand the social and ethical implications of Artificial Intelegence (AI) on future corporate governance, including human oversight in the application of AI itself. The aim of this study is to analyze how three international media outlets, DQ India, The Independent and Business Insider, portray the adoption of AI-based Chief Executive Officer or abbriviated as CEO's in the context of corporate governance. Using Entman's framing analysis, it identifies the themes, narratives and ideologies in the news about AI in corporate governance and examines how differences in media ideology influence the view of this technology. Stakeholder and shareholder theory is used to identify how the media connects AI to traditional theories in the world of corporate identity. The findings reveal the existence of the media's political economy as the main axis, showing that DQ India views AI as a solution to improve operational efficiency and reduce reliance on human managers. In contrast, The Independent takes a more cautious view, considering the potential risks and ethical implications of AI adoption. Business Insider, on the other hand, focused on the financial benefits that companies can realize by using AI in business management.Keyword: Corporate Identity; Digital Leadership; Framing Analysis; Political Economy of Media; Stakeholder Theory.ABSTRAKDi era serba digital saat ini perlu ada pendekatan yang lebih kritis dalam memahami dampak sosial dan etika Kecerdasan Artifisial (AI) dalam kepemimpinan masa depan, termasuk pengawasan manusia dalam penerapan AI itu sendiri. Penelitian ini bertujuan untuk menganalisis bagaimana tiga media internasional, DQ India, The Independent, dan Business Insider, membingkai adopsi Chief Executive Officer (CEO) berbasis AI dalam konteks kepemimpinan perusahaan. Penelitian ini menggunakan Analisis Framing Entman, diarahkan untuk mengidentifikasi tema, narasi, dan ideologi yang terkandung dalam berita tentang AI dalam kepemimpinan, serta bagaimana perbedaan ideologi media mempengaruhi perspektif terhadap teknologi ini. Teori pemangku kepentingan dan pemegang saham digunakan untuk melihat bagaimana media menghubungkan AI dengan teori tradisional terkait identitas korporasi. Hasilnya menunjukkan adanya pusara ekonomi politik media sebagai poros utama yang menunjukkan bahwa DQ India memandang AI sebagai solusi untuk meningkatkan efisiensi operasional dan mengurangi ketergantungan pada manajer manusia. Sebaliknya, The Independent menyajikan pandangan yang lebih hati-hati dengan mempertimbangkan potensi risiko dan penerapan etis dari adopsi AI. Sementara itu, Business Insider fokus pada manfaat finansial yang dapat diperoleh perusahaan dengan mengadopsi AI dalam kepemimpinan.Kata Kunci: Analisis Pembingkaian; Ekonomi Politik Media; Identitas Korporasi; Kepemimpinan Digital; Teori Pemangku Kepentingan